The Effects of Dilated Cardiomyopathy and Atrial Fibrillation Lamin A/C Mutations on Phosphorylated Kinase C Alpha Cellular Distribution and Activity - Mohamed-Uvaize, Musfira (Université d'Ottawa / University of Ottawa, 2014)
Dilated Cardiomyopathy (DCM) with conduction disease and Atrial Fibrillation (AF) are the two cardiac-specific diseases associated with lamin A/C gene (LMNA) mutations. Protein Kinase C Alpha, (PKCα) functions as a nodal integrator of cardiac contractility by “sensing” intracellular calcium and signal transduction. PKCα has been implicated in heart failure and cardiac hypertrophy. Moreover, abnormal PKCα function results in irregular atrial potassium channel activity associated with chronic AF PKCα is a lamin A/C binding partner. Thus, the deregulation of PKCα signaling can contribute to the development of DCM and AF. Our hypothesis is that the AF (Thr528Met), DCM-associated (Arg541Cys) and (Arg541Gly) and DCM/AF-associated (Tyr481Stop) LMNA variants will disrupt the cellular distribution of PKCα therefore resulting in impaired PKCα function. The first objective was to phenotypically characterise Arg541Cys LMNA variant in murine skeletal myoblasts cell line (C2C12) in comparison to cellular phenotypes induced by LMNA variants associated with AF, DCM and DCM with AF. Arg541Cys lamin A and C variants formed circular and sickle-shaped lamin A/C in the nucleus of C2C12 cells. The second objective was to determine the effect of these lamin variants on cellular distribution of PKCα in C2C12 cells. PKCα mislocalized into the nucleus of C2C12 cells transfected with AF and DCM-associated variants (Thr528Met and Arg541Cys). Colocalization analysis showed significant increase in PKCα in the nucleus of AF (Thr528Met) and DCM (Arg541Cys) variants when lamin A and C, were co-transfected compared to wild-type, DCM (Arg541Gly) and DCM/AF (Tyr481Stop) variants. Densitometry analysis showed statistically significant increase in phosphorylated PKCα, the active form of PKCα, in nuclear and cytoplasmic extracts of C2C12 cells expressing Arg541Cys variant. Densitometry analysis also showed statistically significant increase in non-phosphorylated PKCα in the nuclear extract of Thr528Met variant expressing cells. The third objective was to determine the effect of AF and DCM-associated variants on the activity of PKCα. PKCα activity is quantified by measuring the phosphorylation of a known phosphorylated PKCα substrate. Alpha-6-tubulin phospho (Ser165) is phosphorylated by PKCα. Hence, this was used to quantify PKCα activity. No statistical significance was observed in the level of phosphorylated alpha-6-tubulin at (Ser165) in the C2C12 cells that were transfected with lamin A and C variants compared to wild type. Furthermore, PKCα phosphorylation state is cyclic in nature and this could have had an impact on the phosphorylation state of the chosen substrate in this study. The functional consequence of nuclear translocation of PKCα with respect to laminopathies is unknown. Abnormal activation of the Jun N-terminal kinase (JNK) and extracellular signal-regulated kinase (ERK1/2) which are branches of the mitogen-activated protein kinase (MAPK) signalling cascade in hearts of mice, and humans prior to the onset of cardiomyopathy. These findings have been associated to cardiac disease-causing lamin A/C alteration to signal transduction pathways implicated in heart function and cardiomyopathy. Human LMNA cardiomyopathy, could lead to abnormal activation of MAPK signalling pathways via abnormal PKCα activation in cardiomyocytes.
Keywords: Lamin A/C; Dilated Cardiomyopathy; PKC alpha; Laminopathies; Genetics